PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK DANAMON DIVISI SEMM AREA NGAWI - Febriawan Ardi Nugroho; Marsono .; Misnan . (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2017)
Aware of the elements of human resources is a determining factor in the achievement of the company, the employee must doing a good job so that produce a good performance and provider maximum benefit for the company. To make employees perform their jobs well, the company has made various efforts one form review policies on human resources. This research for analysis the influence of organizational culture, leadership and work motivation to the employees of PT Bank Danamon Division SEMM Area Ngawi. The benefits of this research is to facilitate the management to conduct an internal evaluation so that the performance of employees of PT Bank Danamon Division SEMM Area Ngawi continues to growth.